Implementasi Kurikulum Merdeka Dalam Pendidikan Indonesia: Kajian Literatur - Syafriani, Dewi; Dawolo, Berlinda Dwi Purnama; Butar Butar, Leli Andriani; Batubara, Nuraina; Silitonga, Sriwindi (Yayasan Abdurrauf Cendekia Nusantara, 2025)
This research aims to examine the implementation of the Merdeka Curriculum in Indonesian education through a literature review approach. The Merdeka Curriculum is the latest educational policy that emphasizes competency-based learning, differentiation, and strengthening the profile of Pancasila students. The research method used is a literature study by reviewing scientific articles, books, regulations, and recent research reports published between 2020 and 2025. The results of the study indicate that the Merdeka Curriculum has great potential in improving the quality of learning through flexible planning, teacher empowerment, and character development of students. However, its implementation still faces various challenges, such as the readiness of educators, limitations of facilities, and quality disparities among educational units. This article contributes to providing a comprehensive overview of the dynamics of implementing the Merdeka Curriculum while also offering recommendations for strengthening teacher capacity, equalizing facilities, and enhancing monitoring and evaluation so that this policy can be effectively implemented. Thus, this literature review is expected to serve as a reference for academics, education practitioners, and policymakers in formulating more optimal implementation strategies. Abstrak: Penelitian ini bertujuan untuk mengkaji implementasi Kurikulum Merdeka dalam pendidikan Indonesia melalui pendekatan kajian literatur. Kurikulum Merdeka merupakan kebijakan pendidikan terbaru yang menekankan pembelajaran berbasis kompetensi, diferensiasi, dan penguatan profil Pelajar Pancasila. Metode penelitian yang digunakan adalah studi literatur dengan menelaah artikel ilmiah, buku, regulasi, serta laporan penelitian terkini yang terbit antara tahun 2020–2025. Hasil kajian menunjukkan bahwa Kurikulum Merdeka memiliki potensi besar dalam meningkatkan kualitas pembelajaran melalui fleksibilitas perencanaan, pemberdayaan guru, serta pengembangan karakter siswa. Namun demikian, implementasinya masih menghadapi berbagai tantangan, seperti kesiapan tenaga pendidik, keterbatasan sarana prasarana, serta kesenjangan kualitas antar satuan pendidikan. Artikel ini berkontribusi dalam memberikan gambaran komprehensif mengenai dinamika pelaksanaan Kurikulum Merdeka sekaligus menawarkan rekomendasi penguatan kapasitas guru, pemerataan fasilitas, dan penguatan monitoring serta evaluasi agar kebijakan ini dapat berjalan efektif. Dengan demikian, kajian literatur ini diharapkan dapat menjadi rujukan bagi akademisi, praktisi pendidikan, dan pembuat kebijakan dalam merumuskan strategi implementasi yang lebih optimal.